2017
DOI: 10.1097/mao.0000000000001594
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Perimodiolar Electrode Position for Psychoacoustic Discrimination in Cochlear Implantation

Abstract: Perimodiolar electrodes could be a better solution in terms of pitch discrimination both because they are closer to the modiolus and because their impedance is lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…As previous publications show [23,30], the electrode distance influences electrode discrimination. In this research, we also provide more empirical evidence in support of the hypothesis that the electrode distance to the inner wall of the cochlea is a significant variable for the prediction of electrode discrimination ability.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…As previous publications show [23,30], the electrode distance influences electrode discrimination. In this research, we also provide more empirical evidence in support of the hypothesis that the electrode distance to the inner wall of the cochlea is a significant variable for the prediction of electrode discrimination ability.…”
Section: Discussionmentioning
confidence: 69%
“…That has a big impact on the patient hearing workload, and higher workload means fatigue at the end of the day. Several studies have demonstrated that removing poorly discriminated electrodes from a subject's processor map resulted in improved speech recognition scores in some subjects [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that impedances were lower the closer the electrode array was to the modiolus, albeit with a monopolar configuration and not four-point (19–21). High basal impedances have been previously reported for perimodiolar implants; however, the cause was not identified by Tykocinski et al (7), who excluded modiolar proximity as a primary cause.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is more prominent in lateral wall implants than perimodiolar implants and may be a result of electrode positioning. CI532 devices are designed to closely hug the medial wall, with the electrode contacts facing the medial wall to be closer to the modiolus and provide better neural stimulation and pitch discrimination (19). Because the electrode contacts are in close proximity to the medial wall, the spread of the applied current is directed into bone, reducing the influence of the cross-sectional area of the scala on 4PIs.…”
Section: Discussionmentioning
confidence: 99%